2021
DOI: 10.1155/2021/9142364
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of GST-π in Lung Cancer Stem Cell Cisplatin Resistance

Abstract: Background. Cancer stem cells (CSCs) are responsible for tumorigenesis, chemoresistance, and metastasis. Chemoresistance is a major challenge in the management of lung cancer. Glutathione-sulphur-transferase-π (GST-π) plays an important role in the origin and development of various types of cancer by regulating the cellular redox balance. Recent investigations have demonstrated that GST-π is associated with the chemoresistance of lung CSCs (LCSCs). However, the mechanism of GST-π in lung cancer, particularly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Once cells are stimulated by cytokines, radiative, oxidative, or other types o stress, GSTP1 dissociates from JNK, and the activated JNK mediates phosphorylation o c-Jun, a member of the activated protein-1 (AP-1) transcription complex. Phosphorylated c-Jun, in turn, regulates biological processes such as cell proliferation and apoptosis [59] It has been confirmed that GSTP1 is highly expressed in a variety of cancer cells [60][61][62][63] which is considered an essential mechanism of multidrug resistance to chemotherapeutic because suppression of JNK leads to the prevention of apoptosis. GSTA1 and GSTM1 can also form protein complexes with JNK in a mechanism similar to GSTP1, but their inhibi tory activity against JNK is rather weak [2,36].…”
Section: Jnk Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Once cells are stimulated by cytokines, radiative, oxidative, or other types o stress, GSTP1 dissociates from JNK, and the activated JNK mediates phosphorylation o c-Jun, a member of the activated protein-1 (AP-1) transcription complex. Phosphorylated c-Jun, in turn, regulates biological processes such as cell proliferation and apoptosis [59] It has been confirmed that GSTP1 is highly expressed in a variety of cancer cells [60][61][62][63] which is considered an essential mechanism of multidrug resistance to chemotherapeutic because suppression of JNK leads to the prevention of apoptosis. GSTA1 and GSTM1 can also form protein complexes with JNK in a mechanism similar to GSTP1, but their inhibi tory activity against JNK is rather weak [2,36].…”
Section: Jnk Signaling Pathwaymentioning
confidence: 99%
“…MDR is defined as loss of sensitivity to antineoplastic drugs with distinct structures and different molecular targets. Many mechanisms have been proposed to explain MDR, such as the decrease in intracellular drug concentrations due to efflux pump induction, the mutation of drug targets, the upregulated metabolic detoxification, and the enhanced DNA damage repair function [63]. The mechanism of drug resistance may involve a variety of proteins.…”
Section: Gsts and Tumor Multidrug Resistancementioning
confidence: 99%